PEMBELAJARAN MODEL JIGSAW MAMPU MENINGKATKAN HASIL BELAJAR TETAPI BELUM MAMPU MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA - Yusuf Abdullah; Subandi Subandi; Aman Santoso (Jurnal Pembelajaran Sains, 2017)
The aims of the study on learning carbon compound by jigsaw model are to know (1) the differences in learning outcomes (cognitive and affective) among students who were given the assignments of making MM, with students who were given assignment of making summary; (2) the differences of high-level thinking skills among students who were given assignment of making MM with students who were given assignment of making summary. This research used quasi-eksperimental pretest-posttest control group design, using two classes as a research subject. One class with assignments of making MM and another class with the assignment of making summary. The learning carbon compound by jigsaw model has showed that: (1) the class with the assignment of making MM, have higher learning outcomes than the class with making summary assignment; (2) there was no difference in high-level of thinking skills among students who were assigned to making MM with students who were assigned to making summary.